2014
DOI: 10.1179/1754762814y.0000000077
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of neurocognitive processing subtypes with language performance in young children with cochlear implants

Abstract: Neurocognitive skills, specifically cognitive sequencing, serial ordering, and auditory-verbal memory may be targets for therapeutic intervention. Intensive cognitive and educational habilitation and in milieu intervention may improve language learning in children with CIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…79 Sequence processing tasks that do not entail memory include sequential matrix reasoning tests, for which individuals select a response option that completes a sequence of several previous steps, 80 and motor sequencing tests such as fingertip tapping. 10 Although delays and disturbances in sequential processing have been reported in some people with a cochlear implant on tests of spatial memory and fingertip tapping, 9,81 this is not always the case, particularly with spatial memory tests. 74,75,78 As with executive functioning, large individual differences in sequential processing skills within the population with cochlear implants necessitate an individualised patient-centred approach to assessment.…”
Section: Clinical Assessment Of Neurocognitive Outcomesmentioning
confidence: 99%
“…79 Sequence processing tasks that do not entail memory include sequential matrix reasoning tests, for which individuals select a response option that completes a sequence of several previous steps, 80 and motor sequencing tests such as fingertip tapping. 10 Although delays and disturbances in sequential processing have been reported in some people with a cochlear implant on tests of spatial memory and fingertip tapping, 9,81 this is not always the case, particularly with spatial memory tests. 74,75,78 As with executive functioning, large individual differences in sequential processing skills within the population with cochlear implants necessitate an individualised patient-centred approach to assessment.…”
Section: Clinical Assessment Of Neurocognitive Outcomesmentioning
confidence: 99%
“…Congenitally deaf children with cochlear implants (CIs) provide an opportunity to test the Auditory Scaffolding Hypothesis, which has led to a growing literature on sequence processing and learning in deaf individuals (Bharadwaj & Mehta 2016; Conway et al 2009, 2011; Hall et al 2017; Levesque et al 2014; Torkildsen et al, 2018; Ulanet et al 2014). The earliest studies testing the Auditory Scaffolding Hypothesis focused on learning sequential patterns presented within an artificial grammar.…”
Section: Introductionmentioning
confidence: 99%
“…Other researchers have provided additional evidence of sequential processing deficits in deaf individuals, in support of the Auditory Scaffolding Hypothesis. Ulanet et al (2014) reported that children with CIs who demonstrated language delays had concurrent deficits on sequential processing tasks. Bharadwaj and Mehta (2016) showed that children with CIs had poor visuo-motor sequential processing.…”
Section: Introductionmentioning
confidence: 99%
“…It can therefore be challenging to tease apart the impact of hearing (i.e., access to and processing of auditory input) from the impact of language (i.e., access to and processing of linguistically structured input). Several authors have recently proposed that hearing-or lack thereof-has consequences far beyond the auditory system, extending to high-level cognitive processes, including but not limited to executive function (EF; Arlinger, Lunner, Lyxell, & Pichora-Fuller, 2009;Conway, Pisoni, Anaya, Karpicke, & Henning, 2011;Conway, Pisoni, & Kronenberger, 2009;Kral, Kronenberger, Pisoni, & O'Donoghue, 2016;Kronenberger, Beer, Castellanos, Pisoni, & Miyamoto, 2014;Kronenberger, Pisoni, Henning, & Colson, 2013;Pisoni, Conway, Kronenberger, Henning, & Anaya, 2010;Ulanet et al, 2014). A major limitation of these proposals is that they have not excluded the hypothesis that the observed difficulties might be due to problems with language that are only secondary to hearing loss.…”
mentioning
confidence: 99%